Sleep Medicine: Parasomnias - Bollu, Pradeep C. (Mo Med, 2018)
Parasomnias are abnormal and undesirable behaviors during sleep and are thought to be due to the sleep state instability. Some of them are benign, while some of them point to a possible underlying neurodegenerative process. This article briefly discusses the clinical characteristics, demographics, and pathophysiology of major parasomnias and associated disorders. The classification outlined in this article conforms to the current version of International Classification of Sleep disorders.